2017
DOI: 10.4049/jimmunol.1600334
|View full text |Cite
|
Sign up to set email alerts
|

A20 Ameliorates Intracerebral Hemorrhage–Induced Inflammatory Injury by Regulating TRAF6 Polyubiquitination

Abstract: Reducing excessive inflammation is beneficial for the recovery from intracerebral hemorrhage (ICH). Here, the roles and mechanisms of A20 (TNFAIP3), an important endogenous anti-inflammatory factor, are examined in ICH. A20 expression in the PBMCs of ICH patients and an ICH mouse model was detected, and the correlation between A20 expression and neurologic deficits was analyzed. A20 expression was increased in PBMCs and was negatively related to the modified Rankin Scale score. A20 expression was also increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 37 publications
3
42
0
1
Order By: Relevance
“…However, in our heme knowledge graph the connections between IRAKs, TRAF6, and TAB proteins were missing ( Figure 4A). By taking a closer look at these effectors in the context of heme, we found various information for example TRAF6 indicating both a direct and indirect link to heme-induced signaling via TLRs (Hama et al, 2012;IJssennagger et al, 2012;Park et al, 2014;Huang et al, 2015;Meng et al, 2017). In contrast, other effector molecules such as IRAK and TAB proteins (Figure 4) were not described in heme signaling so far.…”
Section: Dissection Of the Crosstalk Between Heme And Tlr Using Hemekgmentioning
confidence: 95%
“…However, in our heme knowledge graph the connections between IRAKs, TRAF6, and TAB proteins were missing ( Figure 4A). By taking a closer look at these effectors in the context of heme, we found various information for example TRAF6 indicating both a direct and indirect link to heme-induced signaling via TLRs (Hama et al, 2012;IJssennagger et al, 2012;Park et al, 2014;Huang et al, 2015;Meng et al, 2017). In contrast, other effector molecules such as IRAK and TAB proteins (Figure 4) were not described in heme signaling so far.…”
Section: Dissection Of the Crosstalk Between Heme And Tlr Using Hemekgmentioning
confidence: 95%
“…Quantitative Real-Time PCR Using our previously described method to isolate total RNA and perform qRT-PCR (Meng et al, 2017), tissue and cellular RNA were extracted using TRIzol (Invitrogen, Carlsbad, CA) and RNA was reverse transcribed into cDNA (Takara, Dalian, China). Quantitative RT-PCR was performed on an ABI PCR instrument (ABI, CA, United States) using iQ SYBR Green reagent.…”
Section: Immunohistochemistry Stainingmentioning
confidence: 99%
“…Following methods described in the literature (Meng et al, 2017), the number of dead rats was counted once every hour after ICH. To calculate the survival rate, the following equation was used: (number of ICH rats per group -number of dead rats per group)/number of ICH rats per group.…”
Section: Survival Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that TRAF6 plays important roles in regulating host immunity, embryonic development, tissue homeostasis, and neurodegenerative disease [18,19]. Our previous study revealed that TRAF6 polyubiquitination may participate in secondary inflammatory injury in a mouse model of intracerebral hemorrhage [20]. Meanwhile, TRAF6 expression has been reported to be upregulated in the peripheral blood of ischemic stroke patients, as well as in neurons from a rat model of cerebral I/R [21].…”
Section: Introductionmentioning
confidence: 98%